RELATIONSHIP BETWEEN PARENTING SATISFACTION AND PARENTING STYLES OF WORKING MOTHERS IN A UNIVERSITY IN MALAYSIA - Maulida Shanti Yusuf; Chee Chew Sim (State Islamic University (UIN) Ar-Raniry, 2016)
The trend of working mothers is not uncommon anymore, starting from a desire to improve the economic status of the families to the desire for self-actualization, combined with the increasing number of women with higher education. Malaysian women comprise 50% of the work force, and 70% of them are married working women (Sabil & Marican, 2010). Mother and child interaction is very important for the development of the child. Each of the working mothers’ parenting style chosen must be appropriate for their children, in accordance with the dual responsibilities or roles that she is juggling with. A working mother who is not able to guide and give full attention to their children might have a negative impact on the child’s developmental outcomes. Thus, this study aimed to look at the relationship between parenting satisfaction and parenting style of working mothers. This study was conducted with 62 working mothers in Sultan Idris Education University who work for an average of 15-32 hours per week. They were 22-40 years old with children under 15 years old. These mothers completed the Parenting Satisfaction Scale (PSS) as a measure of parenting satisfaction and the Parenting Style Dimensions Questionnaire (PSDQ) to measure their parenting styles. The results of this study indicated that the working mothers tended to adopt the authoritative parenting style in their parenting practice, and the majority reported moderate level of parenting satisfaction. The results also showed there were differential relationships between parenting style and parenting satisfaction in the working mothers.